2022
DOI: 10.1039/d1nr06088k
|View full text |Cite
|
Sign up to set email alerts
|

Carrier dynamics at trench defects in InGaN/GaN quantum wells revealed by time-resolved cathodoluminescence

Abstract: Time-resolved cathodoluminescence offers new possibilities for the study of semiconductor nanostructures – including defects. The versatile combination of time, spatial, and spectral resolution of the technique can provide new insights...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 46 publications
1
12
0
Order By: Relevance
“…17 Indeed, research into this material system continues because the internal quantum efficiency drops significantly with increasing emission wavelength (the ‘green gap’), 17 a process which has been attributed to intrinsic field effects, alloy fluctuations and nonradiative defects. 18,19…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…17 Indeed, research into this material system continues because the internal quantum efficiency drops significantly with increasing emission wavelength (the ‘green gap’), 17 a process which has been attributed to intrinsic field effects, alloy fluctuations and nonradiative defects. 18,19…”
Section: Resultsmentioning
confidence: 99%
“…17 Indeed, research into this material system continues because the internal quantum efficiency drops signicantly with increasing emission wavelength (the 'green gap'), 17 a process which has been attributed to intrinsic eld effects, alloy uctuations and nonradiative defects. 18,19 The internal electric elds lead to shis in the electronic bands (band bending) at the interfaces, because the Fermi level is pinned at the surface, and therefore a measurement of band bending in a depth-resolving fashion would provide useful insights into the electronic structure within the stack, which is a crucial factor in determining device performance. XPS has been used to measure changes in the band bending at the surface with laser photoexcitation, by measuring changes in the binding energy of elemental core levels aer carrier creation with time-resolution and chemical specicity.…”
Section: Ingan/gan Heterostructuresmentioning
confidence: 99%
“…Using a gold photocathode driven by laser pulses and a streak camera for time-resolved detection, they revealed the correlation of local carrier dynamics in GaAs nanostructures with the surface morphology. In parallel with the developments in the laser-driven cathode, advances in ultrafast beam blankers promise a flexible and easily integrated method to generate electron pulses with a broad range of pulse widths and repetition rates, while keeping a good spatial resolution with a typical duration of tens of picoseconds. , In recent years, time-resolved CL with pulsed electron beams in SEM has enabled the dynamic study of exciton diffusion, ,, carrier relaxation, , and excited states of DNA . Currently, time-resolved CL studies performed in TEM have also been reported, , making progress toward elucidating structure–function relations at atomic scales.…”
Section: Review Of CL Nanoscopymentioning
confidence: 99%
“…31) Additionally, In atoms diffusing from the mask and the vapor phase also gathered at the corner, resulting in the formation of pits, which might be related to local slips similar to InGaN-film-related trench defects. 32,33) Room-temperature CL spectra were sampled in the spot mode at the center of a single platelet for each series from 1 to 4. The spectra of GaN platelet samples (series 1a and 1b) showed strong yellow luminescence (YL) attributed to the excitation of GaN below the platelets.…”
mentioning
confidence: 99%